1.9k views
0 votes
Y−3=2(x+1) Complete the missing value in the solution to the equation.

User Jmetcalfe
by
5.9k points

2 Answers

3 votes

Answer:

Therefore, y = 2x + 5 is the equation.

Explanation:

The given equation is y - 3 = 2 ( x + 1 )

and we have to simplyfy to get the value of y.

y - 3 = 2 ( x + 1 )

y - 3 = 2x + 2

Now we will add 3 on both the sides of the equation

(y-3) + 3 = (2x + 2) + 3

y = 2x + 2 + 3

y = 2x + 5

Therefore, y = 2x + 5 is the equation.

User Steve Pitchers
by
5.6k points
0 votes

y−3=2(x+1)

distribute

y-3 = 2x+2

add 3 to each side

y = 2x+2+3

y = 2x+5

User Danielassayag
by
5.7k points